Targeted RNA-based therapies for Mucopolysaccharidosis - Santos, Juliana Inês (2021)
Over the last years, most of our work has been focused on the development of alternative, RNAbased therapies for a number of Lysosomal Storage Disorders (LSD), being Mucopolysaccharidosis (MPS) one of the most relevant. Currently, there are two major research lines being pursued: the first relies on the design of mutation-specific approaches to correct abnormal splicing processes in LSD-related genes whenever they underlie pathology and the second depends upon selective downregulation of one gene involved in the very early stages of the glycosaminoglycans’ (GAG) biosynthethic cascade to promote substrate reduction in MPS diseases. There are substantial differences between these two approaches, but they also face common challenges. Two major possible drug types, depending on the genotype that underlies pathology, are being used: U1snRNA and siRNAs. U1snRNAs are specifically designed to overcome particular splicing mutations. These RNA drugs are, therefore, mutation-specific and constitute patient-tailored approaches. We have already demonstrated in fibroblasts that a modified U1snRNA vector (comprising exon 1 to exon 3) designed to improve the definition of exon 2 5’ SDS of the HGSNAT can restore the splicing defect caused by the mutation c.234+1G>A, that leads to MPSIIIC disease (Matos et al., 2014). Currently, our goal is to evaluate in vivo the therapeutic potential of that modified U1 snRNA by testing it in mice expressing the human splicing defect. A preliminary assay was performed and showed promising results. The second group of RNA drugs, siRNAs, holds a different potential. By acting over the GAGs’ biosynthethic cascade, siRNAs will promote an overall decrease of the accumulating substrate. So far, we have already tested this approach in MPSIII patients’ fibroblasts and the overall results are quite promising. We observed a high inhibition of the XYLT1 (a gene that encodes an enzyme involved in an early stage of the HS biosynthetic cascade) mRNAs (around 80%) and a decrease in GAGs storage (only assessed for types C and D until now). Currently, we are evaluating the effect of that decrease on the overall GAGs storage 7 days post-transfection, also with promising results. Here we present an overview on our results with both approaches on MPS diseases.